Concise Review: Altered Versus Unaltered Amniotic Membrane as a Substrate for Limbal Epithelial Cells. (23rd March 2018) - Utheim, Tor Paaske; Aass Utheim, Øygunn; Salvanos, Panagiotis; Jackson, Catherine J.; Schrader, Stefan; Geerling, Gerd; Sehic, Amer
Abstract : Limbal stem cell deficiency (LSCD) can result from a variety of corneal disorders, including chemical and thermal burns, infections, and autoimmune diseases. The symptoms of LSCD may include irritation, epiphora, blepharospasms, photophobia, pain, and decreased vision. There are a number of treatment options, ranging from nonsurgical treatments for mild LSCD to various forms of surgery that involve different cell types cultured on various substrates. Ex vivo expansion of limbal epithelial cells (LEC) involves the culture of LEC harvested either from the patient, a living relative, or a cadaver on a substrate in the laboratory. Following the transfer of the cultured cell sheet onto the cornea of patients suffering from LSCD, a successful outcome can be expected in approximately three out of four patients. The phenotype of the cultured cells has proven to be a key predictor of success. The choice of culture substrate is known to affect the phenotype. Several studies have shown that amniotic membrane (AM) can be used as a substrate for expansion of LEC for subsequent transplantation in the treatment of LSCD. There is currently a debate over whether AM should be denuded (i.e., de-epithelialized) prior to LEC culture, or whether this substrate should remain intact. In addition, crosslinking of the AM has been used to increase the thermal and mechanical stability, optical transparency, and resistance to collagenase digestion of AM. In the present review, we discuss the rationale for using altered versus unaltered AM as a culture substrate for LEC.